Polystyrene/titanium dioxide nanocomposite prepared by sol-gel method at low temperature for small energy bandgap - Hamzah, Maytham Qabel (2022)
Titanium dioxide (TiO2) nanomaterial is broadly employed as an effective photocatalysis semiconductor due to its comprehensive energy band structure. Unfortunately, the efficiency of this material as a photocatalyst with respect to solar spectrum or visible light as the energy source is highly hindered by its wide bandgap and crystal structure. The synthetic methodology for controlling the crystal structure and tuning the TiO2 bandgap has been investigated in this study. Moreover, results showed that TiO2 crystalization is first tunable by polystyrene (PS) acting as a precursor, preventing TiO2 nanomaterials from aggregating. Later, it was found that the bandgap of TiO2 was very much tuneable with the variation of hydrogen peroxide (H2O2) volume (0 mL, 6 mL, and 12 mL) added during the synthesis process. The further process is focused on using only 12 mL of H2O2 has positively depleted the bandgap of PS/TiO2 from 3.49 eV to 3.3 eV. Additional depletion of TiO2 bandgap values to 2.6 eV, 2.52 eV, and 2.47 eV after calcination and hydrothermal treatment of 450°C, 600°C, as well as 750°C were performed. In this research, 100% rutile crystalization of TiO2 was successfully fabricated at a lower temperature [750°C] compared to current literature, where the calcination and hydrothermal treatment transformation of the PS/TiO2 to TiO2 crystal structure from mixed-phase to single-phase rutile matches with the X-ray diffraction (XRD) and Raman Spectroscopy analysis. This study concludes that PS as precursor material prevents agglomeration of TiO2 nanomaterials, while H2O2 and Tetrahydrofuran (THF) assist the binding of TiO2 nanomaterials. On the other hand, calcination and hydrothermal controlled the sizes and bandgaps of TiO2 nanomaterials. The potential application of this research finding includes photocatalyst material and strategies for tuning the crystallisation of nanomaterials